2021
DOI: 10.1111/1462-2920.15439
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the genes encoding the catalytic steps corresponding to LRA4 (l2‐keto‐3‐deoxyrhamnonate aldolase) and l‐lactaldehyde dehydrogenase in Aspergillus nidulans: evidence for involvement of the loci AN9425/lraD and AN0544/aldA in the l‐rhamnose catabolic pathway

Abstract: Summary l‐rhamnose is found in nature mainly as a component of structural plant polysaccharides and can be used as a carbon source by certain microorganisms. Catabolism of this sugar in bacteria, archaea and fungi occurs by two routes involving either phosphorylated or non‐phosphorylated intermediates. Unlike the corresponding pathway in yeasts, the metabolic details of the non‐phosphorylated pathway in filamentous fungi are not fully defined. The first three genes (lraA, lraB and lraC) of the non‐phosphorylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Using a genetic approach, we recently demonstrated a novel and crucial role for the alc regulon gene aldA in the LRA pathway for L-rhamnose catabolism in which its gene product (ALDH) catalyses the conversion of L-lactaldehyde to lactate [14]. Expression of the alc genes in the presence of ethanol is mediated by the transcriptional activator AlcR, and acetaldehyde is its co-inducer.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Using a genetic approach, we recently demonstrated a novel and crucial role for the alc regulon gene aldA in the LRA pathway for L-rhamnose catabolism in which its gene product (ALDH) catalyses the conversion of L-lactaldehyde to lactate [14]. Expression of the alc genes in the presence of ethanol is mediated by the transcriptional activator AlcR, and acetaldehyde is its co-inducer.…”
Section: Discussionmentioning
confidence: 99%
“…The latter is derived from ethanol via the activity of the alcohol dehydrogenase ADHI and then converted by ALDH to acetate, which is subsequently assimilated into central metabolism as acetyl-CoA. We recently reported genetic evidence for a novel and essential role for the aldA gene product in Lrhamnose catabolism [14]-the conversion of L-lactaldehyde to lactate-and in this regard it is noteworthy that earlier biochemical studies of ALDH showed it to be an enzyme of broad rather than narrow aldehyde substrate specificity [24,29]. We also demonstrated previously that the physiological inducer of rhamnose utilisation is an intermediate of the LRA pathway [13].…”
Section: The Alda67 Loss-of-function Mutation Affects the Expression ...mentioning
confidence: 99%
See 3 more Smart Citations